Montenegro : Beyond the Peak, Growth Policies and Fiscal Constraints, Public Expenditure and Institutional Review - World Bank (Washington, DC, 2012)
In 2007, Montenegro was one of the world's fastest growing non-oil economies. The country reaped the benefits from its comprehensive, pre-independence reform program. After the international recognition of statehood had removed the lingering uncertainty over Montenegro's political status, investors reassessed the country's relative attractiveness as a site for business, responding positively to (i) the implementation of the privatization and structural-reform agenda; (ii) the provision of a low-tax, pro-business environment; and (iii) a clearly defined European perspective. In response, investment surged. Capital inflows from foreign direct investment (FDI), largely absent during the first half of this decade, reached a level of 30 percent of Gross Domestic Product (GDP) in 2006 and 40 percent in 2007, fueling domestic demand and stimulating economic growth. Real GDP grew at double-digit rates in 2007, an outcome that stands in stark contrast to the period of economic anemia characterizing Montenegro's pre-independence years. In this buoyant environment, commercial banks supported private-sector activities with very large increases in credit to the economy. These helped to finance higher imports of goods and services, leading to a rapid widening in the current-account deficit from 8.5 percent of GDP in 2005 to 40 percent in 2007. The economic dynamism, exceeding all (published) projections, resulted in an unexpected abundance of fiscal revenues and with generally effective control over public expenditures in 2007, a very substantial overall surplus.